Utility Benchmarking : Public Reporting of Service Performance - Kingdom, Bill; Jagannathan, Vijay (World Bank, Washington, DC, 2012)
In some countries regulators routinely publish indicators of utility service performance through the local media. Exposing the "worst in class" has proven to be a powerful way of pressuring utilities to provide better services to consumers. This Note reviews the requirements for effective benchmarking: choosing indicators that are unambiguous and verifiable, consistent with long-term incentives for good performance, and easy for the public to understand.